고랭지 배추 계약재배 확대를 위한 정책의 우선순위 분석 - 이향미 (한국농촌경제연구원, 2013)
The farming based on contracts with Nonghyup helps make production and consumption predictable. But currently the contract farming is as low as 10% of the total farming. To increase the rate, analyzing the factors that farmers consider when choosing fresh produce distributors is necessary. And the roles of the government and local Nonghyup should be looked into separately. With these in mind, this research identifies relative gravity and priority of evaluation factors that summer chinese cabbage farmers consider when choosing local distributors, and suggests policy priorities through a paired comparison between the government and Nonghyup to help establish contract farming strategies. The method of empirical research used in this study is the AHP analysis for group decision making as multi-stakeholders or multiple decision makers are involved.
Keywords: 계층분석법; 고랭지 배추; 농협; 의사결정; Analytic Hierarchy Process; summer chinese cabbage; National Agricultural Cooperative Federation; decision making